Penguasaan "Blockholder" dan Reputasi Perusahaan di Indonesia Mencangkup Studi Eksploratif: Peranan Nilai Spiritualitas terhadap Corporate Governance, Reputasi Perusahaan dan Kinerja Perusahaan Kelompok LQ-45, Periode 2006-2007 - Majidi, L.M Syahril (Jurnal Aplikasi Manajemen, 2009)
In this research model, there were six variables to analyze, including to local blockholder, foreign blockholder, spirituality values, corporate governance, corporate reputation, and financial performance. The research site were LQ-45 group enterprises in 2006-2007 period. Some 28 wellknown companies in Indonesia used as samples. Spirituality norms and corporate governance measured from internal expectation of the firm, while the corporate reputation was analyzed from external ones (beholders). Blockholder examination constitutes the proportion of stocksholding and the analysis of financial performance in form of Tobins' Q. Through analysis process, it was found that the strongest factor of building spirituality values ​​are human spirituality, and the strongest ones for making corporate governance was corporate's communication. Hypothetical testing results in any findings, such as: 1) spirituality ​had significant effect on corporate governance, 2) the holding of foreign stocks didn't give effect on corporate governance, 3) the property of local Blockholder didn't affect significantly on corporate governance, 4) spirituality values ​​affected significantly on company reputation, 6) corporate governance didn't affect significantly on reputation, 7) the property of local blockholder affected significantly on firm reputation, 8) spirituality values ​​affected significantly financial performance, 9) foreign blockholders gave significant effect on financial performance, 10) reputation didn't affect significantly financial performance, 11) and local blockholders affected significantly on financial performance. These findings indicated that spiritual values ​​played big role in corporate governance, company reputation, financial performance. It was the indication of the occurrence of altruism theory and celestial theory toward any corporations in Indonesia.